The Relationship Between The Level of Anxiety and The Degree of Hypertension In The Elderly At Posyandu Dahlia Karanganom Wonokromo, Pleret District, Bantul Regency: Hubungan Antara Tingkat Kecemasan Dengan Derajat Hipertensi Pada Lansia Di Posyandu Dahlia Karanganom Wonokromo,Kecamatan Pleret Kabupaten Bantul - Salsabila, Fariska Jeny; Rahayu, Bety Agustina; Setyowati, Sri; Isnaeni, Yeni (Ruang Ide Publisher, 2024)
Elderly who experience anxiety or psychosocial stress can increase blood pressure and can even affect the occurrence of hypertension. Uncomfortable body conditions can affect increased cardiac output and arterial vasoconstriction. This can then increase blood pressure. This study aims to determine the relationship between anxiety levels and hypertension levels in the elderly at the Dahlia Karanganom Wonokromo Posyandu, Pleret District, Bantul Regency. This study uses a correlation analysis method with a cross-sectional approach. The population in this study was 41 respondents. Sampling used total sampling and the Kendall's Tau test. Based on the results obtained, most anxiety levels were in the moderate category, amounting to 23 respondents (56.1%), while the majority of hypertension levels were in the grade 1 hypertension category, amounting to 28 respondents (68.3%). The Kendall's Tau test results showed that the p-value = 0.04 <α = 0.05. So, there is a relationship between anxiety levels and hypertension levels in the elderly at the Dahlia Karanganom Posyandu, Wonokromo, Pleret District, Bantul Regency. The majority of grade 1 hypertension with moderate anxiety were 17 respondents (41.5%). There is a relationship between the level of anxiety and the degree of hypertension in the elderly at the Dahlia Karanganom Wonokromo Posyandu, Pleret District, Bantul Regency.